IONPs-induced neurotoxicity via cascade of neuro-oxidative stress, parthanatos-mediated cell death, neuro-inflammation and neurodegenerative changes: Ameliorating effect of rosemary methanolic extract - Arwa A. Elsheikh; Noha Ali Abd-Almotaleb; Mona Mostafa Ahmed; Eman El-Sayed Khayal (Toxicology Reports)
Iron oxide nanoparticles (IONPs) are widely used in various fields, particularly in medicine, where they can be directly injected for diagnostic and therapeutic purposes, although they may induce certain types of toxicity. Therefore, the present work aimed to estimate the potential protective role of the oral extract of rosemary (RO)against the toxic effects of injected IONPs on the brain tissues of adult male rats, and to explore the potential underlying mechanisms involved in reversing such toxicity. Thirty adult male albino rats were allocated into five groups: the control, the vehicle (intravenous saline injection once/week), the RO extract group (orally gavaged100mg/kg/day), IONPs (intravenously injected 30 mg/kg once/week), and the combined RO+IONPs (orally gavaged RO extract 1 hrh before intravenous injection of IONPs). IONPs induced neurotoxicity via triggering a cascade of neuro-oxidative stress, neuro-inflammation, and parthanatos-mediated neuronal cell death by increasing MDA, NO, TNF-α levels, PARP-1, AIF, and NF-κB mRNA expression alongside reducing GSH levels. These incidents contributed to neurodegenerative changes, reflected in increased mRNA expression of α-S, β-APP, and TDP-43. Additionally, IONPs induced structural degenerative changes and elevated iron levels in brain tissues reduced occludin expression, and disrupted the BBB. Furthermore, the concurrent oral RO extract alleviated these conditions and repaired BBB by increasing the occludin expression and ameliorating structural changes in brain tissues. Consequently, the current data provide evidence that RO supplementation during IONP administration holds promise to minimize potential health risks, which should be corroborated by translational studies.